A bimetallic PtPd hybrid nanostructure-amplified enzyme-free conductometric immunoassay for lipocalin-2 in renal cell carcinoma on an interdigitated micro-comb electrode. Issue 15 (27th March 2020) - Huang, Chaoqun; Zhang, Fengling; Wang, Qingshui; Lin, Yao; Huang, Jiyi
Abstract : A new enzyme-free conductometric immunoassay based on bimetallic PtPd hybrid nanostructures was developed for the sensitive determination of lipocalin-2 in renal cell carcinoma. Abstract : A new enzyme-free conductometric immunoassay based on bimetallic PtPd hybrid nanostructures was developed for the sensitive determination of lipocalin-2 in renal cell carcinoma. An immunosensor was prepared by immobilizing the capture antibody on an interdigitated micro-comb electrode, whereas bimetallic PtPd hybrid nanostructures were utilized for the conjugation of the detection antibody. Initially, a sandwich immunoreaction was carried out between the capture antibody and detection antibody in the presence of lipocalin-2 on the functional interdigitated micro-comb electrode. Thereafter, the immobilized PtPd bimetallic nanostructures could be used as enzymatic mimics to catalyze the reaction of hydrogen peroxide (H2 O2 ) in 0.01 M phosphate buffer solution (pH 7.4) containing KI, thereby resulting in the local variation in the conductivity of the modified electrode. Several labeling strategies using Pt nanoparticles, Pd nanoparticles and bimetallic PtPd hybrid nanostructures were investigated for the detection of lipocalin-2, and improved analytical features were acquired with PtPd bimetallic nanostructures. With the PtPd labeling method, the factors influencing the analytical performance of the conductometric immunoassay were studied in detail. The strong attachment of biomolecules to the interdigitated micro-comb electrode and PtPd bimetallic nanostructures enabled a good repeatability and intermediate precision down to 10.4%. The dynamic concentration range spanned from 10 pg mL −1 to 30 ng mL −1 with a low detection limit of 5.9 pg mL −1 lipocalin-2 under optimum conditions. The reliability of the conductometric immunoassay was verified for the detection of lipocalin-2 in 4 blood serum and 4 urine samples and matched well with that obtained from the commercial lipocalin-2 enzyme-linked immunosorbant assay kit.